2020
DOI: 10.1016/j.ejro.2020.100293
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography evaluation of fat infiltration ratio of the multifidus muscle in chronic low back pain patients

Abstract: Background and objectives Fat infiltration of multifidus muscle is an important parameter to assess the efficacy of spinal stabilization training in chronic low back pain (LBP) patients. As a CT scan shows a specific attenuation value for fat, it can be used as a ratio to evaluate fat infiltration of the muscle relative to its cross-sectional area. This study aims to compare the fat infiltration ratio of multifidus muscle between subjects with and without chronic LBP in Indonesia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To evaluate the quality of the lumbar muscles, fat infiltration (FI), CT and MRI are commonly utilized. Although MRI is more commonly used, several previous studies have used CT for the evaluation of FI and reported the reliability of CT evaluation [6][7][8][9]. The CSA and FI of the lumbar muscles are associated with age, sex, body mass index (BMI), and LBP [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the quality of the lumbar muscles, fat infiltration (FI), CT and MRI are commonly utilized. Although MRI is more commonly used, several previous studies have used CT for the evaluation of FI and reported the reliability of CT evaluation [6][7][8][9]. The CSA and FI of the lumbar muscles are associated with age, sex, body mass index (BMI), and LBP [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The multifidus is important as it provides segmental stability and functions as a dynamic stabilizer of the lumbar spine. 3 Previous studies 4,5 showed a significant increase in the cross--sectional area of the multifidus muscle after eight weeks of spinal stabilization exercise compared to the pre-exercise status. It is generally believed that muscular insufficiency and LBP are related, although the primary direction of this relationship is unclear.…”
Section: Introductionmentioning
confidence: 90%
“…1,2 Examination of the total cross-sectional area of the multifidus muscle using Magnetic Resonance Imaging (MRI) has been used to assess the effectiveness of selective spinal stabilization exercises in patients with chronic low back pain (LBP). 3 The role of the paraspinal muscles in the origin of LBP remains unclear. [1][2][3][4][5] There are indications that the multifidus muscles are susceptible to the different pathologies in LBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of muscle with fat is well-known to indicate decreased muscle quality. This can be observed with CT, with fat-infiltrated muscle demonstrating decreased attenuation as compared to non-fatty muscle ( Prasetyo et al, 2020 ). However, this attenuation is not specific to the most metabolically significant fat component, IMCL.…”
Section: Introductionmentioning
confidence: 99%